Etnografi virtual kritik satire video YouTube’s Got Talent di kanal Skinnyindonesian24 - Razanah Mutiara Rysan; Syifa Syarifah Alamiyah; Dyva Claretta; Zainal Abidin Achmad (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2021)
The declining quality of YouTube content created by content creators in Indonesia has received satirical criticism by Skinnyindonesian24 by viewing three video series entitled YouTube's Got Talent. This study aims to analyze the types of satire criticism on the three videos and explore the pros and cons of the quality of satire criticism from Skinnyindonesian24 subscribers. This qualitative research uses a virtual ethnographic approach by virtually interviewing five informants, namely Fadlilah Nur Ramdani or @fdlh.rmdn, Ilham Pratama Rysan or @ilhampratamar, Salsabila Hanifah or @chacash, Wahyu Zulfi or @wahyuss, and Aisyah Ramadhani or @aisyahajagt. In addition, the researchers were involved in a participatory virtual chat through the comment’s column on the Skinnyindonesian24 Youtube account. The satire content on Youtube's Got Talent video shows that YouTube's program culture is like a TV show that contains 'gimmicks' and 'settings' that deceive the audience for the benefit of the content creators. YouTube has experienced the stereotype of content creators with beautiful faces and beautiful bodies. YouTube viewers are more interested in content that is not important but fun, content with dramatic effects, or sexual things. This study concludes that the satire criticism in Youtube's Got Talent video follows the current conditions of the YouTube world in Indonesia. Skinnyindonesian24 provides education to YouTube content creators in Indonesia to create more quality content and not just achieve the number of viewers and subscribers.